2019
DOI: 10.1093/mnras/stz1049
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric mass-loss from high-velocity giant impacts

Abstract: Using moving mesh hydrodynamic simulations, we determine the shock propagation and resulting ground velocities for a planet hit by a high velocity impactor. We use our results to determine the atmospheric mass loss caused by the resulting ground motion due to the impact shock wave. We find that there are two distinct shock propagation regimes: In the limit in which the impactor is significantly smaller than the target (R i << R t ), the solutions are self-similar and the shock velocity at a fixed point on the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…We note that the results obtained in this section are in accord with the numerical simulations presented in [30], which found that for the three dimensional impact problem, the shock decelerates roughly asẊ ∝ m −2/3 (where m is the swept up mass) for γ = 5/3, where the model presented here predicts δ = −0.64. The model here also explains impact experiments, although the translation between the theoretical results and the experimental results is not straightforward.…”
Section: Boundary Conditionssupporting
confidence: 88%
See 3 more Smart Citations
“…We note that the results obtained in this section are in accord with the numerical simulations presented in [30], which found that for the three dimensional impact problem, the shock decelerates roughly asẊ ∝ m −2/3 (where m is the swept up mass) for γ = 5/3, where the model presented here predicts δ = −0.64. The model here also explains impact experiments, although the translation between the theoretical results and the experimental results is not straightforward.…”
Section: Boundary Conditionssupporting
confidence: 88%
“…What's incredible about the impulsive piston problem is that the relation between the shock velocity and the swept up mass v ∝ m δ holds also in the three dimensional impact problem [30], i.e. a power law with the same exponent δ.…”
Section: Impulsive Piston Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…This simulation is supposed to represent a normal cratering event. We chose the adiabatic index to be 𝛾 = 1.4, since this value best describes the high pressure shock behaviour in silica (Yalinewich & Schlichting 2019). Since we want to resolve the impactor and also follow the shock wave to distances much larger than the impactor radius, we arranged 20,000 mesh generating points in a non-uniform way inside the computational domain.…”
Section: Numerical Simulationsmentioning
confidence: 99%